First‐order integral switching surface sliding‐mode control method of active front end rectifier for fast charger applications. Issue 17 (28th January 2021) - Nahavandi, Ramin; Asadi, Mehdi; Guerrero, Josep M.
Abstract : This study proposes a control technique based on integral switching surface sliding‐mode control for three‐phase pulse‐width modulation (PWM) rectifier. The proposed control system is based on the combination of a conventional proportional–integral (PI) controller and with two decoupled first‐order sliding‐mode (PI‐FOSM) current controller. A set of integral switching surfaces based on the state‐space equation are designed in the internal loop to force the grid currents to track their desired values. The proposed control approach improves the transient response and minimises the steady‐state error under uncertainty. In addition, a conventional PI controller is also employed for the voltage regulation loop and generating the current reference of inner loops. In the controller design, all parameters of the system are considered with bounded perturbations in the design of control law. The main advantage of the proposed controller is robustness property against variations of entertained PWM rectifier parameters and external disturbances. The proposed PI‐FOSM can improve transient performance and can decrease of the harmonic components under steady‐state condition. In order to validate the theoretical contributions of this study, the performance of the proposed controller has been investigated by using a prototype laboratory.